Aesthetics of Text: Creative and Transfigurative Langue (in Theory) - Rugg, Stephen P. (Lumen et Vita, 2017)
Theory remains a dirty word in Biblical Studies; deconstruction often is received with glazed glances of irrelevance or outright rejection. I propose to offer a philosophically relevant and theologically potent reading of Genesis 1:1 based on the trivium disciplines of grammar, logic, and rhetoric. This reading will echo the Transfiguration of Jesus in the synoptic Gospels. The weight of interpretation will focus on the use of the Hebrew direct object marker (אֵת) as a visual symbol of langue (roughly, language); אֵת is composed of the first (aleph) and last (tav) consonants, allowing for it to be a merism for the alphabet and a symbol of language. The rhetorical disarticulation of grammar allows for a transformative reading of a biblical description of creation: “At the beginning [of time] God created langue, the heavens and the earth with langue.” The combination of time and langue establishes parole (speech), which becomes instantiated in the speech-act of the Divine through the breath/spirit of God: “Let there be light,” etc. The text, and indeed its very letters, becomes the locus for an aesthetic reflection that offers theological relevance to all linguistic arts. The “ever excelling” bubbling of language transforms human creativity into a divine imitation and transfigures the world in its wake. We can insist that the grammatical reading of the Genesis text remains, as does the logical presentation of creatio ex nihilo. But, informed by Roman Jakobson and Paul de Man, rhetoric offers the opportunity to break open the text, revealing potential meaning in both the visualization of symbolic form and in the openness of the text to transcendence. The rhetorical wounding allows the text to become an open mouth (Derrida), ever speaking and evading the enclosure of grammar and logic.